Isotope composition of winter precipitation and snow cover in the foothills of the Altai - N. S. Malygina; A. N. Eirikh; N. Yu. Kurepina; T. S. Papina (Лëд и снег)
Over the past three decades, several general circulation models of the atmosphere and ocean (atmospheric and oceanic general circulation models  – GCMs) have been improved by modeling the hydrological cycle with the use of isotopologues (isotopes of water) HDO and H2 18O. Input parameters for the GCM models taking into account changes in the isotope composition of atmospheric precipitation were, above all, the results obtained by the network GNIP – Global Network of Isotopes in Precipitation. At different times, on the vast territory of Russia there were only about 40 simultaneously functioning stations where the sampling of atmospheric precipitation was performed. In this study we present the results of the isotope composition of samples taken on the foothills of the Altai during two winter seasons of 2014/15 and 2015/16. Values of the isotope composition of precipitation changed in a wide range and their maximum fluctuations were 25, 202 and 18‰ for δ18О, dexc and δD, respectively. The weighted-mean values of δ18О and δD of the precipitation analyzed for the above two seasons were close to each other (−21.1 and −158.1‰ for the first season and −21.1 and −161.9‰ for the second one), while dexc values differed significantly. The comparison of the results of isotope analysis of the snow cover integral samples with the corresponding in the time interval the weighted-mean values of precipitation showed high consistency. However, despite the similarity of values of δ18О and δD, calculated for precipitation and snow cover, and the results, interpolated in IsoMAP (from data of the GNIP stations for 1960–2010), the dexc values were close to mean annual values of IsoMAP for only the second winter season. According to the trajectory analysis (the HYSPLIT model), the revealed differences between both, the seasons, and the long-term average values of IsoMAP, were associated with a change of main regions where the air masses carrying precipitation were formed, namely, the North Atlantic (the winter season of 2014/15) and the inland areas with open ice-free water bodies (the season of 2015/16). Thus, with the correct interpretation of the results, the data on the snow cover isotope composition on the Altai foothills can be used as an alternative data sources instead of the GNIP data.